Maternal perceptions of supervision in preschool-aged children: a qualitative approach to understanding differences between families living in affluent and disadvantaged areas - Ablewhite, Joanne; Kendrick, Denise; Watson, Michael; Shaw, Ian (Cambridge University Press, 2015)
Aim: To explore maternal perceptions of supervision and childhood unintentional injury in order to develop understanding and explanation for differences in unintentional injury rates between an advantaged and disadvantaged area. Background: Unintentional injury is the second cause of mortality and a significant cause of morbidity in the zero to four year age group. Children living in socio economic disadvantage are at a greater risk of unintentional injury than their more affluent counter-parts. Methods: Qualitative study using semi-structured interviews; content data analysis was undertaken. Participants included 37 mothers with a child aged less than five years; 16 living in an area of disadvantage (and high rate of childhood unintentional injury) and 21= living in an advantaged area (and low rate of childhood unintentional injury). Findings: Parents in both areas described the importance of parental supervision in reducing child unintentional injury risks. Parents in both areas used listening as a supervision strategy. Parents in both areas described how ‘when the child goes quiet’ that is a cue for them to make a visual check on the child. Listening was used more for boys than girls in both areas, but parents in the advantaged area used listening as a supervision strategy more frequently than those in the disadvantaged area. Parents described supervision strategies as being shaped by child character and age rather than child gender. Parents in both areas described similar strategies for managing distractions. An important difference was found with regard to older siblings; parents living in the advantaged area described older siblings as an injury risk to younger children. Parents in the disadvantaged area described older siblings as providing some supervision for younger children. Parents living in disadvantaged circumstances may face greater challenges with regard to supervision than parents living in advantaged circumstances and this may partly explain differences in injury risk.